Analisis Lima Dimensi Religius dalam Film Qodrat Karya Charles Gozali: Kajian Sosiologi Sastra - Tambunan, Rieke Dinda Laila; Umam, Khothibul; Khurosan, Herpin Nopiandi (Program Studi Sastra Indonesia, Fakultas Ilmu Budaya, Universitas Diponegoro, 2025)
AbstractThis study uses a material object in the form of Charles Gozali's Qodrat film. Charles Gozali's Qodrat film has a unique aspect in its religiosity. This study uses narrative film theory, literary sociology theory and religiosity which are explained using descriptive methods. The purpose of this study is to explain the narrative structure of the film contained in Charles Gozali's Qodrat film. The theory of narrative structure is used to describe the story and plot, the relationship between narrative and space, the relationship between narrative and time, and the main elements of the narrative (characters, problems and conflicts, and goals), and themes in the Qodrat film. Meanwhile, to eliminate the value of religiosity in the film Qodrat by Charles Gozali, the author uses the theory of the dimensions of religiosity of Glock and Stack. The results of the analysis of the narrative structure of the film Qodrat by Charles Gozali. The results of the analysis of the narrative structure of the film Qodrat by Charles Gozali are the discovery of several developments in the character's faith through analysis of the story and plot, the relationship between narrative and space, the relationship between narrative and time, the main elements of the narrative and theme. The results of the analysis obtained are that the film Qodrat meets the five aspects of the theory of religiosity of Glock and Stack. The five dimensions consist of five dimensions of religiosity, namely the dimensions of belief (belief/belief), practice (ritual/religious practice), knowledge (knowledge), experience (experience), and consequences (consequences), Belief in the existence of God, understanding of the help and protection given by God, religious rituals performed to God such as prayer, ruqyah and fasting, knowledge of religion, ability to read the holy verses of the Qur'an, understand the science of rukiah, and be able to fight against jinn disturbances, spiritual experiences, mystical disturbances, and receive help from God, the dimension of consequences includes the end that will be obtained from the actions taken, in the form of good and bad.Keywords: Qodrat film, sociology of literature, dimensions of religiosity, Glock and Stark IntisariPenelitian ini menggunakan objek material berupa film Qodrat karya Charles Gozali. Film Qodrat karya Charles Gozali memiliki keunikan pada aspek religiusitasnya. Penelitian ini menggunakan teori naratif film, teori sosiologi sastra dan religiusitas yang dijelaskan dengan metode deskriptif. Tujuan penelitian ini adalah untuk menjelaskan struktur naratif film yang terdapat dalam film Qodrat karya Charles Gozali. Teori struktur naratif digunakan untuk mendeskripsikan cerita dan plot, hubungan naratif dengan ruang, hubungan naratif dengan waktu, serta elemen pokok naratif (pelaku cerita/tokoh, permasalahan dan konflik, dan tujuan), serta tema dalam film Qodrat. Sedangkan untuk menganalisis nilai religiusitas dalam film Qodrat karya Charles Gozali, pengarang menggunakan teori dimensi religiusitas Glock dan Stack. Hasil analisis struktur naratif film Qodrat karya Charles Gozali. Hasil analisis struktur naratif film Qodrat karya Charles Gozali ini adalah ditemukannya beberapa perkembangan keimanan tokoh melalui analisis cerita dan plot, hubungan naratif dengan ruang, hubungan naratif dengan waktu, elemen pokok naratif dan tema. Adapun hasil analisis yang didapatkan bahwa film Qodrat memenuhi lima aspek teori religiusitas Glock dan Stack. Lima dimensi tersebut, terdiri dari lima dimensi religiusitas yaitu dimensi belief (kepercayaan/keyakinan), practice (ritual/praktik keagamaan), knowledge (pengetahuan), experience (pengalaman), dan consequences (konsekuensi), Keyakinan terhadap adanya Tuhan, keyakinan terhadap pertolongan dan perlindungan yang diberikan Tuhan, ritual keagamaan yang dilakukan kepada Tuhan seperti sholat, ruqyah serta berpuasa , pengetahuan tentang agama, kemampuan dalam membaca ayat suci al-Qur’an, memahami ilmu rukiah, serta mampu melawan gangguan jin, pengalaman-pengalaman spiritual, gangguan-gangguan mistis, serta mendapat pertolongan dari Tuhan, dimensi akibat meliputi akhir yang akan diperoleh atas tindakan yang dilakukan, berupa baik dan buruk.Kata kunci: film Qodrat, sosiologi sastra, dimensi religiusitas, Glock dan Stark